Southern Ocean link between changes in atmospheric CO2 levels and northern-hemisphere climate anomalies during the last two glacial periods. (15th February 2020) - Gottschalk, Julia; Skinner, Luke C.; Jaccard, Samuel L.; Menviel, Laurie; Nehrbass-Ahles, Christoph; Waelbroeck, Claire
Abstract: Past millennial-scale changes in atmospheric CO2 (CO2, atm ) concentrations have often been attributed to variations in the overturning timescale of the ocean that result in changes in the marine carbon inventory. Yet, there remains a paucity of proxy evidence that documents changes in marine carbon storage globally, and that links them to abrupt climate variability in the northern hemisphere associated with perturbations of the Atlantic Meridional Overturning Circulation (AMOC). The last two glacial periods were suggested to differ in the spatial extent of the AMOC and its sensitivity to perturbations. This provides an opportunity to compare the nature of marine carbon cycle-climate feedbacks between them. Here, we reconstruct variations in respired carbon storage (via oxygenation) and the AMOC "geometry" (via carbonate ion saturation) in the deep South Atlantic. We infer decreases in deep South Atlantic respired carbon levels at times of weakened AMOC and rising CO2, atm concentrations during both glacial periods. These findings suggest a consistent pattern of increased Southern Ocean convection and/or air-sea CO2 fluxes during northern-hemisphere stadials accompanying AMOC perturbations and promoting a rise in CO2, atm levels. We find that net ocean carbon loss, and hence the magnitude of CO2, atm rise, is largely determined by the stadial duration. North Atlantic climate anomalies therefore affect Southern Ocean carbon cycling in a consistent manner, through oceanic (e.g., ventilation seesaw) and/or atmospheric processes (e.g., Ekman pumping). Highlights: Comparison of South Atlantic carbon cycle dynamics during the last two glacials. Observed respired carbon changes parallel millennial-scale CO2, atm variability. Possible links to northern-hemisphere stadials and AMOC changes are identified. Ocean carbon loss during millennial-scale events is proportional to stadial durations. Proxy data-model comparison highlights a strong role of Southern Ocean ventilation.